Relevansi Industri 4.0 dan Society 5.0 Terhadap Pendidikan Di Indonesia - Felixtian Teknowijoyo; Leni Marpelina (Educatio, 2022)
This research aims to analyze the industrial revolution 4.0 and 5.0 and its relevance to education in Indonesia. Research methods using literature studies that review or critically review the knowledge, ideas, or findings contained in journals, books, and other scientific works The results of research show that the presence of the industrial revolution 4.0 and 5.0 contributed significantly to Indonesian education. One of them is the existence of technology-based learning innovations that make it easier for students to learn without knowing space, time, and place. Industry 4.0 is technology-driven, society 5.0, however, is value-driven. The former requires the latter to remind society's essential needs, values, and responsibilities as the primary target; The latter requires the former for a technological push and solution. Therefore, the development of the Industrial Revolution 4.0 and 5.0 is expected to bring progress to the development of education, especially in Indonesia, by creating change and preparing superior and innovative graduates with skills that have been prepared in advance.